PENERAPAN BLENDED LEARNING PADA KEMANDIRIAN BELAJAR SISWA SEKOLAH DASAR DI MASA PANDEMI COVID-19 - Ayu Sutera Widyaningsih (Universitas Muhammadiyah Purwokerto, 2023)
The background of this thesis research is the existence of a virus outbreak that has occurred throughout the world, one of which is the country of Indonesia, namely the Covid-19 pandemic which has had an impact on the education sector which has resulted in all schools switching to distance or online learning. The purpose of this research is to find out how the application of blended learning can increase student learning independence. The method used is descriptive qualitative method with data collection methods, observation, interviews and study documentation. The results of this study are that the teacher has applied the blended learning model at Citra Indonesia Elementary School, both from this blended learning, students are able to increase their learning independence. The results of this study are expected to be useful for related parties who can benefit from them, such as schools, teachers, parents and further researchers.The background of this thesis research is the existence of a virus outbreak that has occurred throughout the world, one of which is the country of Indonesia, namely the Covid-19 pandemic which has had an impact on the education sector which has resulted in all schools switching to distance or online learning. The purpose of this research is to find out how the application of blended learning can increase student learning independence. The method used is descriptive qualitative method with data collection methods, observation, interviews and study documentation. The results of this study are that the teacher has applied the blended learning model at Citra Indonesia Elementary School, both from this blended learning, students are able to increase their learning independence. The results of this study are expected to be useful for related parties who can benefit from them, such as schools, teachers, parents and further researchers.